2007
DOI: 10.1016/j.intcom.2006.08.006
|View full text |Cite
|
Sign up to set email alerts
|

A model of cognitive loads in massively multiplayer online role playing games

Abstract: Being one of the most commercially successful entertainment software applications, massively multiplayer online role playing games (MMORPGs) continue to expand in term of the revenue they generate as well as the involvement of users who congregate in their virtual space and form communities around them to support each other. Unlike conventional offline computer games, or networked games with limited numbers of players, MMORPGs are not merely software applications as they are usually seen as a space with compli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
1
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(48 citation statements)
references
References 15 publications
3
40
1
4
Order By: Relevance
“…Two studies were qualitative, with a qualitative observational study focusing on the cognitive overloads of players (Ang et al 2006), and the other an analysis of players' accounts of their gaming experiences that they had posted to online forums (Chappell et al 2006), both with very small sample sizes (n=3, n=14) and subjective analyses. Only one study involved a brain scan using cases and controls.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two studies were qualitative, with a qualitative observational study focusing on the cognitive overloads of players (Ang et al 2006), and the other an analysis of players' accounts of their gaming experiences that they had posted to online forums (Chappell et al 2006), both with very small sample sizes (n=3, n=14) and subjective analyses. Only one study involved a brain scan using cases and controls.…”
Section: Resultsmentioning
confidence: 99%
“…Studies spanned the years from 2005 to 2009: there were three studies from 2005 (Ko et al 2005;Lo et al 2005;Williams and Skoric 2005); five studies from 2006 (Yee 2006;Chappell et al 2006;Williams 2006;Eastin and Griffiths 2006;Ang et al 2006); three studies from 2007 (Grüsser et al 2007;Wei 2007;Smyth 2007); three studies from 2008 (Hussain and Griffiths 2008;Kim et al 2008;Peters and Malesky 2008); and two from 2009 (Ko et al 2009;Hart et al 2009). …”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Apparently, innovative teaching material design seems highly acceptable to students and could easily generate student learning motivation. (2) To teachers: our research shows that gamification could assist in game-based learning design and translate into a direct effect upon student learning motivation. Consequently, it is suggested that teachers apply gamification teaching aids, in addition to textbooks, to their instruction, so that students may, more productively, review what they have learned through games.…”
Section: Practical Implicationsmentioning
confidence: 92%
“…These multimedia representations reduce the cognitive demands on players' limited capacities and simultaneously develop visual or spatial analysis skills. (Ang, Zaphiris, & Mahmooh, 2007), (de Felix & Johnson, 1993), (Hays, 2005), (Huang et alii, 2013) 10.Feedback Refers to the measurement of achievement during the game. Feedback provides a tool for players to learn from previous actions and adjust accordingly.…”
Section: Telling Storiesmentioning
confidence: 99%